Surface Morphology and Dissolution Rate of Slow Discharge Urea Coated with Starch-Urea-Borax Matrix - Naz, M.Y. (Bellwether Publishing, Ltd., 2014)
Pure starches do not exhibit fast tacking and high viscosity to meet the standards set by many industrial processes. Therefore, the objective of this work was to obtain high- viscosity coating solutions after modifying tapioca starch with urea as a cross-linker and borax as a thickener. Study of the physical properties confirmed that the prepared solutions were exhibiting more pronounced non-Newtonian behavior. A shear-thinning behavior followed by shear-thickening was observed for all solution compositions. At room temperature, the critical shear rate at which the transition from shear-thinning to shear-thickening occurred was ranging from 45.8 to 78Â sâ1. However, the shear-thickening response to the applied shear rate was less prominent at higher temperatures. The surface tension and density of the solutions were found to decrease monotonically with an increase in temperature. Once the physical properties were fully understood, 1, 1.5 and 2Â mL of each solution were used to coat 30Â g of urea fluidized above its minimum level of fluidization. The phenomenological analyses of the coated and uncoated urea samples were carried out by understating their surface morphology, coating thickness, percent coating, dissolution rate, percent release and crushing strength. It was concluded that the coating thickness, percent coating, dissolution rate and percent release increase over time with an increase in solution volume and borax mass; however, some random results were obtained while investigating the effects of the solution volume on the crushing strength. The highest crushing strength was noticed for urea samples coated with 1.5Â mL of solution followed by 1Â mL, 2Â mL and without coating. Â© 2014, Copyright Taylor & Francis Group, LLC.